Design thinking : integrating innovation, customer experience and brand value. - Lockwood, Thomas, ....- (New York : Allworth, 2010)
Design Thinking is packed with intriguing case studies and practical advice from industry experts. This anthology is organized into three sections that focus on the use of design for innovation and brand-building, the emerging role of service design, and the design of meaningful customer experiences. This book provides readers with the strategies necessary to encourage the creative thought process in their companies, which will ultimately help to cultivate innovation, and therefore boost business. Experienced design leaders share their personal stories and give specific examples of their companies' forward-thinking creations. This unique approach helps the reader learn how to build a solid brand foundation, solve problems with simplified thinking, anticipate and capitalize on trends, figure out what consumers want before they do, and align mission, vision, and strategy with a corporate brand. A sense of the content within Design Thinking can be gained from the titles of some of the key essays: "Building Leadership Brands," "The Designful Company," "Brand Building by Service Design," "Service Design Via the Global Web," "Customer Loyalty," and "Driving Brand Loyalty on the Web".